Time reversal acoustics - Gan, Woon Siong (Springer, 2021)
This book highlights time reversal acoustics, techniques based on the symmetry properties of acoustic fields. It has the unique feature that the first eleven chapters of the book are on the in depth studies of the theories of time reversal acoustics. The remaining chapters are on the four major applications of time reversal acoustics, together with their experimental setups and case studies: underwater communication, seismic exploration, nondestructive evaluation, and medical ultrasound imaging. The gauge invariance approach to acoustic fields, proposed by the author in 2007, is confirmed by the successful fabrication of acoustical metamaterials and the applications of time reversal acoustics to super resolution. The book also presents groundbreaking applications of time reversal acoustics to underwater communication technology and the application of metamaterials to time reversal acoustics.